Manajemen Alokasi Dana Desa Di Desa Sibedi Kecamatan Marawola Kabupaten Sigi Provinsi Sulawesi Tengah - Nasir Mangngasing; Irianto Irianto; Filo Leonardo Tinggogoy (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2021)
The basis of this research is qualitative while the type of research used in this research is descriptive qualitative. The technique of withdrawing informants as many as 5 people who are considered to have knowledge of, Village Fund Allocation Management (ADD) in Sibedi Village, Marawola District, Sigi Regency, Central Sulawesi Province, Data collection techniques are carried out in two ways, namely library research and field studies consisting of observation, interviews and documentation. The method used in this research is using qualitative analysis methods. Based on the research results obtained by researchers from interviews with informants and facts in the field that from the aspect of planning, organizing, actuating dimensions are good, but in the controlling dimension the results are not optimal, so the authors conclude that the Village Fund Allocation Management (ADD) in Sibedi Village, Marawola District Sigi Regency, Central Sulawesi Province, in order to further strive for the ability to provide services to communities in villages, it means that the activities carried out are more focused on controlling based on agreed policies and rules, so that the duties and functions of the apparatus in serving are in accordance with what is expected.